ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS APARATUR DESA (ANALYSIS OF FACTORS AFFECTING THE EFFECTIVENESS OF VILLAGE APPARATUS) - irham iskandar iskandar (Inovasi, 2018)
The main purpose of this study is to determine the factors that affect the effectiveness of rural apparatus. The type of research method is research development, namely research aimed at developing research findings or previous theories, both for the purposes of pure science and applied science and so forth. The data used in this study are primary data covering the effectiveness of apparatus, governance, benefits of village funds, silpa and strategy. Secondary data is obtained through the village ministry, the development of underdeveloped areas and transmigration and community empowerment and aceh gampong. The results showed that 1). The results of governance variables in the western and eastern regions are insignificant and have a positive and negative influence on the effectiveness of the village apparatus, while central governance is significant and has a positive effect on the effectiveness of rural apparatus, 2). The results of the rural fund benefit variables in the eastern and central regions are insignificant and have a positive and negative influence on the effectiveness of the village apparatus, while the village fund benefits in the central region are significant and have a positive effect on the effectiveness of the village apparatus, 3). The results of the Silpa variables and strategies in the west, east and central regions are insignificant and have a negative and positive influence on the effectiveness of rural apparatus. Keywords: effectiveness, governance, benefits of village funds, silpa and strategy